Project Retrosight Understanding the returns from cardiovascular and stroke research: The Policy Report - Wooding, Steven (RAND Corporation, 2011)
This work explores impacts of cardiovascular and stroke research funded 15-20 years ago and draws out aspects associated with high or low impact. It describes 29 case studies of grants from Australia, Canada and UK. Policy summary volume.